Comparing the post-traumatic growth levels of Turkish patients with breast and lung cancer - Doğan, Sibel; Şimşek, Cevahir (Wiley-Blackwell, 2016)
[Abstract Not Available]
WOS: 000385942700265
Keywords: Oncology; Psychology; Biomedical Social Sciences